2015
DOI: 10.1016/j.ecss.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Trophic connectivity between offshore upwelling and the inshore food web of Banc d'Arguin (Mauritania): New insights from isotopic analysis

Abstract: M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT2 ABSTRACT Banc d'Arguin (BA), Mauritania, is a nationally protected shallow gulf > 10,000 km 2 between the Sahara desert and the upwelling system off the Mauritanian coast. In the southeast, BA consists of a 500 km 2 tidal flat, the most important wintering site for shorebirds using the East Atlantic Flyway. The Mauritanian upwelling-driven phytoplankton production supports the most productive fisheries worldwide, but little is known about its trophic rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…This is readily evident when looking at the base of the coastal shelf food webs. Coastal systems are energetically supported by a variety of sources, including local benthic or pelagic producers, as well as allochthonous organic matter which may originate either from land via freshwater run-off or from the open sea through tidal currents and upwellings (Nielsen and Navarrete, 2004;Carlier et al, 2015;Christianen et al, 2017;Meunier et al, 2017). Moreover, the proportional contribution of the different energy sources to coastal shelf food webs may also be affected by several human-induced drivers, such as coastal development, seabed disturbance, eutrophication, and changes in river flow (Tewfik et al, 2005;Al-Habsi et al, 2008;Christianen et al, 2017;Hemraj et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is readily evident when looking at the base of the coastal shelf food webs. Coastal systems are energetically supported by a variety of sources, including local benthic or pelagic producers, as well as allochthonous organic matter which may originate either from land via freshwater run-off or from the open sea through tidal currents and upwellings (Nielsen and Navarrete, 2004;Carlier et al, 2015;Christianen et al, 2017;Meunier et al, 2017). Moreover, the proportional contribution of the different energy sources to coastal shelf food webs may also be affected by several human-induced drivers, such as coastal development, seabed disturbance, eutrophication, and changes in river flow (Tewfik et al, 2005;Al-Habsi et al, 2008;Christianen et al, 2017;Hemraj et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen records from West Africa presented in Hély et al (2014) indicate prolonged dry seasons and possibly associated intensified trade winds during the mid-Holocene that could have promoted upwelling along the Mauritanian coast (Talbot, 1981). However, along the inshore Banc d'Arguin corresponding to the location of the palaeoestuary, satellite derived SST and nutrient data depict a notably limited influence of upwelling today (Carlier et al, 2015). A low input of upwelled water to the essentially sheltered inner Banc d'Arguin was further supported by N isotopic signatures in fish and their potential food sources, suggesting very limited supply of upwelled nutrients to inshore species (Carlier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, along the inshore Banc d'Arguin corresponding to the location of the palaeoestuary, satellite derived SST and nutrient data depict a notably limited influence of upwelling today (Carlier et al, 2015). A low input of upwelled water to the essentially sheltered inner Banc d'Arguin was further supported by N isotopic signatures in fish and their potential food sources, suggesting very limited supply of upwelled nutrients to inshore species (Carlier et al, 2015). Considering these observations, temperature variability is likely of lesser importance to the overall δ 18 O composition of these waters in near-shore habitats, particularly for bivalves living within the palaeo-estuary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the food web of this intertidal area is mainly supported by local benthic primary production (i.e. seagrass and microphytobenthos), with low contributions of phytoplankton, macrophytes and epiphytes to the food-web (Wolff et al 1993b, Carlier et al 2015. Being adjacent to the Sahara desert, Banc d'Arguin does not receive freshwater inflow from rivers and precipitation is limited to occasional thunderstorms that occur at irregular intervals, sometimes several years apart (Wolff & Smit 1990, van der Geest et al 2014).…”
Section: Study Sitementioning
confidence: 99%